Statybų sektoriaus smulkių ir vidutinių įmonių ateities e. vizija: e. verslo perspektyva - Gudauskas, Renaldas; Gatautis, Rimantas; Vitkauskaitė, Elena (Information & Media, 2007)
Europos Komisijos finansuojamo e-NVISION projekto tikslas – sukurti naujovišką e. verslo platformą smulkioms ir vidutinio dydžio įmonėms, sudarant joms sąlygas modeliuoti ir pritaikyti savo organizacijose konkrečius e. verslo scenarijus, kurie tenkintų vartotojų ir tiekėjų poreikius. Straipsnyje nagrinėjamas šių scenarijų įgyvendinimas, grindžiamas sprendimais, integruojančiais partnerių reikalavimus atitinkančias paslaugas. Laikomasi į paslaugas orientuotos sprendimų architektūros kūrimo principo, įvertinančio teisinius, ekonominius ir socialinius veiksnius, lemiančius tokio pobūdžio paslaugų įgyvendinimą. Kuriami technologiniai sprendimai siekti bendro tikslo – paskatinti smulkių ir vidutinių įmonių, ypač naujų šalių narių įmonių, dalyvavimą Europos Sąjungos ateities e. verslo scenarijuose.SMEs in construction sector: future business scenariosRenaldas Gudauskas, Rimantas Gatautis, Elena VitkauskaitėSummaryFuture business in Europe will be conducted through flexible networks of interdependent organizations. It will be global, open and collaborative, dynamic and adoptive, frictionless and consistent. Information communication technologies (ICT) will be one of the essential presuppositions for successful business development. All industries will be affected by such kind transformations and construction sector is not an exception.Problem: e-Business use in construction sector is very limited comparing with other industries analysed in e-Business W@tch (2005). Most of companies prefer reactive activities to active ones in terms of ICT use. Such situation might be explained by particularities of services provided and construction processes and by slow penetration of ICT in sector there dominates SMEs. The main objective of EU funded project e-NVISION is the development and validation of an innovative e-Business platform enabling Construction SMEs to model and adapt particular business scenarios; to integrate all their enterprise applications and to incorporate legal, economical, social and cultural services, with the final goal of facilitating their participation in the Future European e-Business Scenario.The aim: to identify most important internal processes of construction SMEs and to evaluate possibilities to use ICT to optimise those processes.